Work and money: payoffs by ethnic identity and gender - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2009)
Upon arrival in the host country, immigrants undergo a fundamental identity crisis. Their ethnic identity being questioned, they can be classified into four states assimilation, integration, separation and marginalization. This is suggested by the ethnosizer, a newly established measure to parameterize a person's ethnic identity, using individual information on language, culture, societal interaction, history of migration, and ethnic self-identification. In what state individuals end up varies among immigrants even from the same country. Moreover, the quest for ethnic identity affects women and men differentially. This paper contends that ethnic identity can significantly affect the attachment to and performance of immigrants in the host country labor market, beyond human capital and ethnic origin characteristics. Empirical estimates for immigrants in Germany show that ethnic identity is important for the decision to work and significantly and differentially affects the labor force participation of men and women. Women who exhibit the integrated identity are more likely to work than women who are German assimilated; this does not hold for men. However, once we control for selection in the labor market and a slew of individual and labor market characteristics, ethnic identity does not significantly affect the earnings of men or women immigrant workers.
urn:nbn:de:101:1-2009082040
Keywords: F22; J15; J16; Z10; 330; Ethnosizer; ethnicity; ethnic identity; immigrant assimilation; integration; ethnic earnings; Migranten; Ethnische Gruppe; Persönlichkeitspsychologie; Soziale Integration; Lohndifferenzierung; Einkommen; Deutschland